PATIENT COMPLAINT MANAGEMENT AS A STRATEGY TO IMPROVE THE QUALITY OF HOSPITAL SERVICES - Fatia Ulfia Putri; Vip Paramarta (RADJA PUBLIKA, 2025)
Patient complaints are an inevitable phenomenon in hospital service delivery and reflect the gap between patient expectations and the reality of the services received. Ineffective complaint management has the potential to reduce public trust, damage the hospital's image, and hinder efforts to improve service quality. This study aims to analyze the role of complaint management as a strategy for improving hospital service quality through a literature review of various scientific articles, books, and health regulations over the past five years. The results of the study indicate that the forms and patterns of patient complaints are generally related to aspects of timeliness, communication quality, administrative procedures, costs, and the attitudes of health workers. Complaint management plays a crucial role in strengthening the quality system through early detection mechanisms for service weaknesses, increasing patient satisfaction, and encouraging organizational change that is more oriented towards the needs of service users. The effectiveness of complaint management is influenced by top management commitment, human resource capacity, clarity of internal regulations, and information technology support.